Report of Task Group 201 of the American Association of Physicists in Medicine: Quality management of external beam therapy data transfer. Issue 6 (23rd April 2021) - Siochi, R. Alfredo; Balter, Peter; Bloch, Charles D.; Santanam, Lakshmi; Blodgett, Kurt; Curran, Bruce H.; Engelsman, Martijn; Feng, Wenzheng; Mechalakos, James; Pavord, Daniel; Simon, Thomas; Sutlief, Steven; et al.
Abstract : With the advancement of data‐intensive technologies, such as image‐guided radiation therapy (IGRT) and intensity‐modulated radiation therapy (IMRT), the amount and complexity of data to be transferred between clinical subsystems have increased beyond the reach of manual checking. As a result, unintended treatment deviations (e.g., dose errors) may occur if the treatment system is not closely monitored by a comprehensive data transfer quality management program (QM). This report summarizes the findings and recommendations from the task group (TG) on quality assurance (QA) of external beam treatment data transfer (TG‐201), with the aim to assist medical physicists in designing their own data transfer QM. As a background, a section of this report describes various models of data flow (distributed data repositories and single data base systems) and general data test characteristics (data integrity, interpretation, and consistency). Recommended tests are suggested based on the collective experience of TG‐201 members. These tests are for the acceptance of, commissioning of, and upgrades to subsystems that store and/or modify clinical treatment data. As treatment complexity continues to evolve, we will need to do and know more about ensuring the quality of data transfers. The report concludes with the recommendation to move toward data transfer open standards compatibility and to develop tools that automate data transfer QA.